PENERAPAN MEDIA VISUAL PAPAN KERANJANG PENGURANGAN TERHADAP MINAT BELAJAR PADA PEMBELAJARAN MATEMATIKA KELAS I SDN PEDURUNGAN KIDUL 01 - Amelia, Natasya Dwi; Ferina Agustini; Tiyas Purnama Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research purpose to describe the application of visual learning media in class I mathematics learning at SDN Pedurungan Kidul 01. This reseacrh was carried out because the lack of interest in learning in class I students can be seen from activities when learning is less active. This reseacrh is a qualitative research with a descriptive appoarch. The location of the research was in class I at SDN Pedurungan Kidul 01 the data analysis techniques use were data collection, data reduction, data presentation, and drawing conclusions. The results of this reserach state that students have different learning interests. Students who have high interest in learning find it easier to understand subtraction material. Students have a moderate interest in learning when learning Mathematics subtraction material using visual medium of the subtraction basket board, they show an interested attitude but on the other hand sometimes get bored while learning. Apart from that, students with low interest in learning tnd to have an attitude that easily gets bored when learning.